Qualifications frameworks and learning outcomes: new challenges for European education and training policy and research - Bohlinger, Sandra [Verfasser] (My University, 2011)
"Qualifications frameworks are political instruments that enable assessing learning outcomes. They describe the relationships between different types of qualifications and learning as well as they promote permeability, transparency and equity between vocational and higher education. Qualifications frameworks are drivers for change since they provide the impetus for a number of fundamental reforms required in (vocational) education and training systems. Focussing on the European Qualifications Framework, this paper addresses the question of whether the development of qualifications frameworks yields the anticipated socioeconomic and political benefits. The aim of the contributation ist to review previous experience with implementing qualifications frameworks and to analyse the current trends and challenges within the European countries." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Berufsbildung; Qualifikationsrahmen; Lernergebnisorientierung; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; EU-Bildungspolitik